Integrasi Data Walktest Sistem Saas Cloud Computing PT. Bentala Sakti Globalindo - Darwin; Fatmasari (LPPM STMIK ANTAR BANGSA, 2019)
Abstract Ã¢â‚¬â€ Cloud Computing is a combination of the use of computer technology (computing) and internet-based (cloud) development. Cloud is a metaphor of the internet, as clouds are often depicted in computer network diagrams. As with the cloud in the computer network diagram, cloud (cloud) in Cloud Computing is also an abstraction of the complex infrastructure that is hidden. It is a computational method in which capabilities related to information technology are presented as a service (as a service), so that users can access it via the internet (in the cloud) without knowing what is in it, experts with it, or have control over the technology infrastructure that helps it.